The Place Of The English Language In The Training Of Sport Executives: Motivational Approach (case Of Higher School Of Sports Science And Technology Students) - Boukhari, Saliha; Amriou, Zouhir (sports creativity, 2025)
The aim of this article, entitled the place of English language in sport executives training, is to study one of the parameters inherent to the teaching/ learning process that is the learner psychological parameter, namely motivation, which could eventually represent one of his difficulties during his English learning process. Our investigation had been led during 2017/2018 and 2018/2019 on the whole ES-STS students (181) to whom we addressed a questionnaire and this, in order to answer to our problematics: How do this concept of motivation influence (or even act upon) the students learning faced with English language? The investigation ’ s results allow us to confirm their non-involvement indeed even their lack of motivation as for this foreign language learning and this, could eventually influence negatively their success.